Experience of 10 years in routine trans operative endoscopy and calibration in fundoplication due to gastroesophageal reflux disease - Sahagun, Cesar Manuel Vargas; Rodríguez, Jorge Alejandro Ortiz De La Peña; Silver, Enrique Jean; De Jesús, Martín Vega; Ibarrola, Antonio Giovanni Spaventa; Vela, Cuauhtémoc Morfin; Zavala, Tomás Benavides; Lopez, Elsa Paulina Alonso (International Journal of Research in Medical Sciences, 2022)
Background: Endoscopy and intraoperative calibration in fundoplication for gastroesophageal reflux disease (GERD), confirm an adequate technique avoiding postoperative failure. Intraoperative changes and morbidity in routine use are unknown. Methods: Retrospective study in a single center, data were taken primarily from electronic archive medical records. A total of 899 who underwent fundoplication surgery with endoscopy and/or routine intraoperative calibration due to GERD met the required criteria between 1 January 2010 and 31 December 2020. The primary objective was to identify the number of calibration and intraoperative endoscopy findings. Also, the morbidity associated with its routine use was analyzed. Results: Over a 10-year study period, the most frequent calibration in the Nissen Fundoplication was 60Fr in 472 cases (61.4 %). The most used calibration in Toupet Fundoplication was 60Fr in 26 cases (21.1%). Endoscopy was performed in 786 patients (71.38%), of which; 3 patients (0.3%) required changes, secondary to fundoplication rotation in 2 patients (0.2%) and redundant gastric fundus in 1 patient (0.1%). Conclusions: Routine intraoperative calibration and endoscopy achieved excellent results in 96.8% of fundoplication’s, ensuring adequate esophageal position and corroborating an adequate intraoperative technique; decreasing the rate of failures and immediate postoperative dysphagia.